THE ROLE OF A COUNTRY’S ECONOMY IN THE DEVELOPMENT OF THE SOCIAL SPHERE (The Conference Hub, 2025)
The development of the social sphere is one of the key indicators of a country’s progress. The advancement of sectors such as education, healthcare, culture, and social protection not only improves the quality of life of the population but also strengthens the intellectual and spiritual potential of the nation. From this point of view, the development of the social sphere is directly linked to the state of the national economy. Without a strong economic base, it is difficult to implement consistent reforms in the social field.